2023
DOI: 10.1038/s41598-023-44853-6
|View full text |Cite
|
Sign up to set email alerts
|

Shared biomarkers and immune cell infiltration signatures in ulcerative colitis and nonalcoholic steatohepatitis

Wenxin Wang,
Xin Gao,
Ning Kang
et al.

Abstract: The coexistence of ulcerative colitis (UC) and nonalcoholic steatohepatitis (NASH) involves a intricate interplay, though the precise pathophysiological mechanisms remain elusive. To shed light on this, our study endeavors to unravel the shared gene signatures and molecular mechanisms by employing quantitative bioinformatics analysis on a publicly available RNA-sequencing database. Gene expression profiles of UC (GSE87466) and NASH (GSE89632) were retrieved from the Gene Expression Omnibus (GEO) database. Diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…Accumulating evidence highlighting the robust association between MAFLD and IBD, the specific molecules and mechanisms underlying this association remain elusive 32 , 33 . Research revealed that decreasing levels of butyric acid could exacerbate damage to the intestinal barrier, affect the liver through leakage through the damaged intestinal barrier, leading to MAFLD 31 .…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating evidence highlighting the robust association between MAFLD and IBD, the specific molecules and mechanisms underlying this association remain elusive 32 , 33 . Research revealed that decreasing levels of butyric acid could exacerbate damage to the intestinal barrier, affect the liver through leakage through the damaged intestinal barrier, leading to MAFLD 31 .…”
Section: Discussionmentioning
confidence: 99%